THE EFFECT OF STIMULATING SEEDS OF FIVE GENOTYPES BY SOAKING THEM WITH GIBBERELLIN ACID ON SOME GROWTH TRAITS OF BREAD WHEAT TRITICUM AESTIVUM. L. (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2024)
The experiment was carried out in the agricultural research and experimentation fields of the College of Agriculture/University of Kirkuk, Shoraw region, for the agricultural season 2018-2019, in order to determine the effect of soaking seeds of five varieties of wheat (Kawz-Kalak-Al-Fayad-Florka-Ibaa 99) with three levels of gibberellin (0.0, 50, and 100). ) mgGA3. L1 - The interaction between these studied factors on growth characteristics and yield components (number of branches - plant height - spike length - number of spikelets per spike - duration of germination crisis - spike weight - biological yield) and the results were as follows:- Increasing the number of branches gave the highest average of 2.59 branches. Plant at a concentration of 50 mg. L1 - while the level gave 0.0 mg. L1 - Gibberellin, the minimum average is 1.5 shta.plant, an increase in plant height, as the highest average gave 55.8 cm at a concentration of 50 mg. L-1) while the level was given as 0.0 mg. L1-) Gibberellin The lowest average for this trait is 48.53 cm, while in Oujda, the highest plant height for the Fayyad and Kalak genotypes reached (56.4 and 55.3) cm, respectively, and the lowest for the parental 99 genotype reached 48.4 cm. An increase in the average spike length occurred when soaked in gibberellin. At a concentration of (50 mg.L-1), the highest average was recorded at 7.1 cm, while the level (0.0 mg.L-1) gave the lowest average of 4.8 cm. It is also evident that an increase in spike length occurred with the Fayyad and Kalak genotypes, as they gave the highest average of 7.6 and 6.6 cm. Respectively, while the genotype of 99 parents gave the lowest average of 4.8 cm, the highest average gave 13.13 spikelets. Sunbulah 1- At the concentration of soaking in gibberellin (50 mg.L-1-) at the time when the comparison treatment (0.0 mg.L-1-) gave the lowest average gibberellin of 9.73 Sunbulah. spikelet -1, while the genotypes Khaos and Fayyad gave the highest spikes, reaching 13.2 and 12.8 spikelets. Spike 1 - respectively, while the two genotypes Florica and Epa 99 gave the lowest average, reaching 9.2 spikelets. Spike 1 - For both genotypes, the concentration of 50 was superior by giving it the shortest period of 12 days, followed by the concentration of 100, which reached 13 days. As for the comparison treatment without addition, it was delayed by 2 days. - 3 days for the two treatments, gibberellin 50 and 100. As for the different genotypes, there were no significant differences between them. The highest spike weight was 0.98 grams at the concentration of soaking in gibberellin )50mg.L-1) while the control treatment (0.0 mg.L-1-) gave gibberellin the lowest average of 0.53 g, while the Fayyad genotype gave the highest amount of 0.97 g while the genotype and the 99 parents gave the lowest average of 0.7 g. Soaking with gibberellin at a concentration of (50 mg.L-1-) gave the highest biological yield of 2.08 g, while the concentration of (0.0 mg.L-1-) gave the lowest gibberellin of 1.11 g. Clack, Fayyad, and Kaus excelled as they gave the highest average (1.8, 1.8, and 1). 6) respectively, at the time when Florca gave the lowest average biological yield of 1.05 g.